The effect of parathyroid hormone on the uptake and retention of 25-hydroxyvitamin D in skeletal muscle cells. Issue 173 (October 2017) - Abboud, M.; Rybchyn, M.S.; Liu, J; Ning, Y; Gordon-Thomson, C.; Brennan-Speranza, T.C.; Cole, L.; Greenfield, H.; Fraser, D.R.; Mason, R.S.
Highlights: Receptors for parathyroid hormone (PTH) were detected in mouse muscle fibers and in differentiated myotubes, but not myoblasts. Pre-incubation of muscle fibers or myotubes with physiological concentrations of PTH, concentration-dependently reduced uptake of labelled 25(OH)D3 . Incubation of myotubes with PTH after uptake of labelled 25(OH)D3 concentration-dependently reduced retention of 25(OH)D3 . While the results indicate that PTH modulates muscle cell uptake and retention of 25(OH)D3, the in vitro system may not be a comprehensive reflection of vitamin D homeostatic mechanisms in vivo. Abstract: Data from our studies, and those of others, support the proposal that there is a role for skeletal muscle in the maintenance of vitamin D status. We demonstrated that skeletal muscle is able to internalise extracellular vitamin D binding protein, which then binds to actin in the cytoplasm, to provide high affinity binding sites which accumulate 25-hydroxyvitamin D3 (25(OH)D3 )[1] . This study investigated the concentration- and time-dependent effects of parathyroid hormone (PTH) on the capacity of muscle cells to take up and release 3 H-25(OH)D3 . Uptake and retention studies for 3 H-25(OH)D3 were carried out with C2C12 cells differentiated into myotubes and with primary mouse muscle fibers as described[1] . The presence of PTH receptors on mouse muscle fibers was demonstrated by immunohistochemistry and PTH receptors were detected in differentiated myotubes, but not myoblasts, and on muscle fibers by Western blot. Addition of low concentrations of vitamin D binding protein to the incubation media did not alter uptake of 25(OH)D3 . Pre-incubation of C2 myotubes or primary mouse muscle fibers with PTH (0.1 to 100 pM) for 3 h resulted in a concentration-dependent decrease in 25(OH)D3 uptake after 4 or 16 h. These effects were significant at 0.1 or 1 pM PTH (p < 0.001) and plateaued at 10 pM, with 25(OH)D3 uptake reduced by over 60% (p < 0.001) in both cell types. In C2 myotubes, retention of 25(OH)D3 was decreased after addition of PTH (0.1 to 100 pM) in a concentration-dependent manner by up to 80% (p < 0.001) compared to non-PTH treated-C2 myotubes. These data show that muscle uptake and retention of 25(OH)D3 are modulated by PTH, a physiological regulator of mineral homeostasis, but the cell culture model may not be a comprehensive reflection of vitamin D homeostatic mechanisms in whole animals.